ELITE WHEAT SEEDS GROWING - K.I.X Aminova Dildor Xolmurodovna (European Journal of Agricultural and Rural Education, 2024)
The article discusses recommendations for the first test of firstyear offspring, second-year test of offspring, breeding nursery in the first year, breeding nursery in the second and third years. The article provides super-elite and elite seed